Extracecellulr vesicles (EVs) microRNAs (miRNAs) derived from mesenchymal stem cells (MSCs) in osteoarthritis (OA); detailed role in pathogenesis and possible therapeutics - Seyede Sara Pakdaman Kolour; Saeide Nematollahi; Masoud Dehbozorgi; Farnaz Fattahi; Fatemeh Movahed; Neda Esfandiari; Mohammad Saeed Kahrizi; Nima Ghavamikia; Bahareh Salmanian Hajiagha (Heliyon)
The primary cause of pain and disability in the world is osteoarthritis (OA), a common joint disease characterized by the primary pathological alteration in articular cartilage deterioration. The general outcome of treatment is not acceptable despite current interventions. Therefore, joint replacement surgery is frequently needed by patients with severe OA. Mesenchymal stem cells (MSCs) have become a practical treatment choice for preclinical and clinical OA palliation in recent years, mainly due to their unique immunomodulatory attributes. Further, attractive candidates for cell-free therapy for OA are MSC-derived extracecellulr vesicles (EVs) that convey bioactive molecules of the original cells, such as microRNAs. These EVs have been shown to significantly influence the regulation of various physiological activities of cells in the joint cavity. Dysregulated miRNAs upregulate the synthesis of enzymes that degrade cartilage, downregulate the expression of components in the cartilage matrix, promote the production of proinflammatory cytokines, induce programmed cell death in chondrocytes, inhibit the process of autophagy in chondrocytes, and participate in pathways related to pain. MiRNAs are also found in extracellular membranous vesicles (EVs), such as exosomes, and play a role in intercellular communication in osteoarthritic joints. Thus, the biosynthesis, chemical makeup, and mechanism of action of miRNAs-enriched EVs in OA are all thoroughly covered in this review. We additionally discussed how miRNA-enriched MSC-EVs might be used therapeutically to change intercellular interaction in OA.